Seasonal changes in the demersal nekton community off the Changjiang River estuary - 姜亚洲 凌建忠 李建生 杨林林 李圣法 (Chinese journal of oceanology and limnology, 2014)
The diversity, community structure and seasonal variation in demersal nekton off the Changjiang （Yangtze） River estuary was evaluated using monthly trawl survey data, collected between December 2008 and November 2009. A total of 95 species （56 teleosts, 11 cephalopods, and 28 decapod crustaceans） from 69 genera, 49 families and 15 orders were collected. These species could be classified into six groups on the basis of temporal distribution patterns. The resident crab Ovalipes punctatus dominated the community, both in number and biomass. A clear seasonal succession was observed in the species composition. Cluster analysis revealed three primary seasonal groups corresponding to the samples collected in winter-spring, late spring-summer and late summer-autumn. The highest biomass and lowest diversity were observed in summer, while the lowest biomass and highest diversity in winter. The abundance-biomass comparison curves and community composition suggested that the investigated community was moderately disturbed. The results suggest that reduction in fishing pressure and in the degree of seasonal hypoxia are essential for sustainable resource management off the Changjiang River estuary.